Características hematológicas, bioquímicas e biométricas de Piaractus mesopotamicus Holmberg, 1887 (Osteichthyes: Characidae) oriundos de cultivo intensivo - Tavares-Dias, Marcos [UNESP] (2004)
Hematological characteristics are important tools for diagnosis and prognostic features in fish population and they contribute to the comprehension of comparative physiology, phylogenetic relation, food habit and other ecological parameters. Red blood cell count (RBC), white blood cell count (WBC), thrombocytes counts, glucose, cortisol, hepatosomatic and splenosomatic relation were evaluated in Piaractus mesopotamicus. The values of hepatosomatic relation varied from 0.67% to 2.79% and splenosomatic relation from 0.011% to 0.108%. RBC 1.870 to 4.590 × 106/μL, hemoglobin concentration 5.7 to 12.1g/dL, haematocrit 24.0% to 40.0%, mean corpuscular volume 98.0 to 174.0 fL, mean corpuscular haemoglobin concentration 19.1 to 34.2g/dL, glucose 40.6 to 89.2mg/dL and cortisol 4.73 to 110.5ng/dL The number of total thrombocytes was 12,160.0 to 89,280.0/μL and WBC 2,019.0 to 47,473.0/μL. Differential count of leucocytes showed 54.1% limphocytes, 10.9% neutrophils, 10.3% monocytes, 9.9% PAS-positive granular leukocytes (PAS-GL), 6.7% eosinophils, 0.3% basophils and 7.8% immature leucocytes. Variation of these haematological characteristics in the same fish species was observed, being considered as the normal variation in the fish concerned. Hence it is incorrect to assume that biological characteristics in fishes are distributed normally.